2012
DOI: 10.1039/c2mb25158b
|View full text |Cite
|
Sign up to set email alerts
|

Label-free quantitative proteomic analysis reveals dysfunction of complement pathway in peripheral blood of schizophrenia patients: evidence for the immune hypothesis of schizophrenia

Abstract: Schizophrenia is a complex mental disease caused by a combination of serial alterations in genetic and environmental factors. Although the brain is usually considered as the most relevant organ in schizophrenia, accumulated evidence suggests that peripheral tissues also contribute to this disease. In particular, abnormalities of the immune system have been identified in the peripheral blood of schizophrenia patients. To screen the serum proteomic signature of schizophrenia patients, we conducted shotgun proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 50 publications
2
60
0
3
Order By: Relevance
“…DAAM2, one of five differentially expressed genes, returned to control levels in the whole blood when people were in remission after their first psychotic episode, suggesting this mRNA could be altered by antipsychotics and may be a potential marker for treatment response. Taken together, there is only downregulation of intercellular adhesion molecule in people with Sz that were replicated in at least two microarray studies [138,140] . Other studies have identified markers that may be of use in identifying people who are at risk of developing the disorder, such as the up-regulation of DEFA in T cells and plasma from people with Sz, and both their affected or unaffected monozygotic twin [136] .…”
Section: The Human Transcriptome and Human Proteome Studiesmentioning
confidence: 89%
See 3 more Smart Citations
“…DAAM2, one of five differentially expressed genes, returned to control levels in the whole blood when people were in remission after their first psychotic episode, suggesting this mRNA could be altered by antipsychotics and may be a potential marker for treatment response. Taken together, there is only downregulation of intercellular adhesion molecule in people with Sz that were replicated in at least two microarray studies [138,140] . Other studies have identified markers that may be of use in identifying people who are at risk of developing the disorder, such as the up-regulation of DEFA in T cells and plasma from people with Sz, and both their affected or unaffected monozygotic twin [136] .…”
Section: The Human Transcriptome and Human Proteome Studiesmentioning
confidence: 89%
“…It is possible that some of the differential patterns reported to exist in people with Sz can be used for diagnostic purposes. However, only a few studies reported the sensitivity and specificity of the discri minability of their markers [108,123,125,130,138,140,141] , leaving doubt as to the potential of the other molecules to act as markers. To try and assess the utility of these disparate markers, performing a metaanalysis based on the categories we used here might be helpful to identify potential markers that have large and consistent effect size across studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On Table 2 are presented the studies published on blood serum and plasma, spanning from 2006; after this search 7 studies on serum of patients with SCZ and 6 on plasma were found. The preferred quantitative method of analysis of the serum samples was label-free MS, using LC-MS E [62][63][64] or MS1 signal intensity [65][66][67]. On the other hand, from the 6 studies in plasma, 5 used 2-DE-MS analysis [50,[69][70][71][72] and one study using targeted mass spectrometry MRM technique to quantify 42 plasma proteins [73].…”
Section: Biomarker Discovery In Peripheral Fluidsmentioning
confidence: 99%